Evaluation Of Type-2 Diabetes Mellitus Among Hepatitis B And C Patients In Penang General Hospital, Malaysia - Hamoodi, Hani Kareem (2011)
Diabetes mellitus (DM) and chronic hepatitis C (HCV) and B (HBV) virus infections are relatively common disorders and considered as worldwide, major public health problems with increasing complication and mortality rates. An epidemiologic link between chronic hepatitis virus infection and diabetes mellitus has recently been reported. Many of previous studies have revealed a higher prevalence of DM in patients with HCV-related chronic liver disease when compared to patients with chronic liver disease resulting from other etiologies